Rapid, Simple, and Sensitive Spectrofluorimetric Method for the Estimation of Ganciclovir in Bulk and Pharmaceutical Formulations - Garima Balwani; Emil Joseph; Satish Reddi; Vibhu Nagpal; Ranendra N. Saha (Journal of Spectroscopy)
A new, simple, rapid, sensitive, accurate, and affordable spectrofluorimetric method was developed and validated for the estimation of ganciclovir in bulk as well as in marketed formulations. The method was based on measuring the native fluorescence of ganciclovir in 0.2 M hydrochloric acid buffer of pH 1.2 at 374 nm after excitation at 257 nm. The calibration graph was found to be rectilinear in the concentration range of 0.25–2.00 μg mL−1. The limit of quantification and limit of detection were found to be 0.029 μg mL−1 and 0.010 μg mL−1, respectively. The method was fully validated for various parameters according to ICH guidelines. The results demonstrated that the procedure is accurate, precise, and reproducible (relative standard deviation <2%) and can be successfully applied for the determination of ganciclovir in its commercial capsules with average percentage recovery of 101.31 ± 0.90.